Sonoanatomy of sensory branches of the ulnar nerve below the elbow in healthy subjects - Kim, Ki Hoon; Lee, Seok Jun; Park, Byung Kyu; Kim, Dong Hwee (Muscle & Nerve, 2018)
ABSTRACT Introduction We identify sensory branches of the ulnar nerve—palmar ulnar cutaneous nerve (PUCN), dorsal ulnar cutaneous nerve (DUCN), and superficial sensory branch—using ultrasonography. Methods In 60 forearms of 30 healthy adult volunteers, the origin and size of the PUCN, DUCN, and superficial sensory branch were measured by ultrasonography. The relative pathway of the DUCN to the ulnar styloid process was also investigated. Results The PUCN was observed in 47 forearms (78%), and the DUCN was observed in all forearms. Average distances from the pisiform to the origin of the PUCN and DUCN were 11.9 ± 1.4 and 7.0 ± 1.0 cm, respectively. Superficial and deep divisions split 0.9 ± 0.3 cm distal to the pisiform. Cross‐sectional areas of the PUCN, DUCN, and superficial sensory branch were 0.3 ± 0.1, 1.5 ± 0.5, and 3.9 ± 1.0 mm2, respectively. Discussion Sensory branches of the ulnar nerve can be visualized by ultrasonography, helping to differentiate ulnar nerve injury originating at either wrist or elbow. Muscle Nerve 57: 569–573, 2018